Constancy of the Proportionate Equilibrium Rate of Growth: Result or Assumption? - Brems, Hans (Review of Economic Studies, 1957)
Journal Article Constancy of the Proportionate Equilibrium Rate of Growth: Result or Assumption? Get access Hans Brems Hans Brems Urbana, Illinois Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 2, February 1957, Pages 131–138, https://doi.org/10.2307/2295766 Published: 01 February 1957